Falhas de Mercado na Atividade Turística: Uma Análise Exploratória da Atuação dos Municípios Portugueses - Costa, Cláudia S. (2018)
This paper presents an exploratory analysis of Portuguese municipalities interventions to solve tourism market failures (public goods, externalities, natural monopolies and asymmetric information). With this purpose, and considering the use of interviews as data collection technique, a case study with five municipalities are carefully examined. The results suggest that Portuguese municipalities used the most policy tools identified in state of the art to mitigate the tourism market failures. Additionally, the results also suggest that Portuguese municipalities increases policy tools to typology specifically aimed at tourism policy.